Attitudes towards missing school to represent Singapore in overseas sporting competition : a study on secondary school athletes - Goh, Hilda Ru Bin (Nanyang Technological University, 2020)
Academics and sport are both important to a student athlete’s career. More often than not, student athletes are expected to be able to handle the rigour of the dual commitment. A huge part of being an athlete is the need to miss classes in order to attend overseas competitions. The purpose of this paper was then to explore the attitudes and experiences of secondary school student athletes when they miss classes to represent Singapore in competitions that are held overseas. Phenomenological semi-structured interviews were conducted with 6 secondary school student athletes who have missed school at least twice to represent Singapore in overseas competitions. The interviews were transcribed verbatim and analysed. Results showed that student athletes feel a variety of emotions before adopting a task-oriented mindset during the pre-competition phase. The competition phase revealed that the athletes had to deal with challenges and overcoming it while juggling their mixed emotions. The post-competition phase showed that athletes had a good sense of responsibility in terms of their commitment to their studies. This study provides useful insights for the relevant institutions to look more into the experiences of a student athlete and to provide the relevant help. Future research can look to expand the scope by focusing on athletes within a different education level.